La double vie du policier ex-hassid dans 160 rue Saint-Viateur Ouest de Magali Sauves - Grossman, Simone (Canadian Jewish Studies / Études juives canadiennes, 2022)
The relationship between Quebecers and Hasidim is portrayed through the investigation of policeman Mathis Blautstein, a homoseuxual ex-Hasid, into the murder of a pesticide inventor, leading to the murder of a young Jewish pianist from Berlin who was smuggled to Montreal in 1940 through the complicity of a Quebec notary. From Montreal to Berlin, the investigation reconstituted the filiations and remedies the shortcoming of history. Les rapports entre Québécois et Hassidim sont représentés à travers l’enquête du policier Mathis Blaustein, ex-hassid homosexuel, sur le meurtre d’un inventeur de pesticides, menant à l’assassinat d’une jeune pianiste juive berlinoise arrivée clandestinement à Montréal en 1941 grâce à la complicité d’un notaire québécois. De Montréal à Berlin, l’enquête reconstitue les filiations et remédie aux manquements de l’Histoire.